Pengaruh Terapi Rebusan Daun Salam Terhadap Penurunan Tekanan Darah Ibu Menopause dengan Hipertensi - Sumiati; Sri R, Ary Oktora; Aifa, Wira Ekdeni; Susanti, Komaria (Universitas Muhammadiyah Surabaya, 2026)
Background: Hypertension is a condition in which blood pressure increases, leading to persistent symptoms in target organs, such as stroke (which occurs in the brain and has a high mortality rate), coronary heart disease (which damages the heart's blood vessels), and left ventricular hypertrophy (which affects the brain and heart). Purpose: This study aims to determine the effect of giving boiled bay leaves on reducing blood pressure in elderly hypertensive women with menopause hypertension. Methods: This type of research is quantitative with a pre- and post-test group design with a control group design. The sample in this study were 38 menopausal mothers with hypertension sufferers in the Kedabu Rapat Community Health Center Working Area as the population. Sampling using a purposive sampling technique covering 16 people. The research data were processed with a paired test statistical test with a value of 0.000 (p <0.05). Results: The results of the study showed that blood pressure after being given boiled bay leaves water was reduced. The average difference in blood pressure reduction between before and after the intervention was obtained from the difference in systolic pressure of 3.73 to 2.20. The results of the Paired t test on systolic pressure p value 0.000 (<0.05) and diastolic pressure p value 0.001 (<0.005). There is an effect of giving boiled bay leaves water on reducing blood pressure in menopausal mothers. Conclusion: So, it can be concluded that giving boiled bay leaves can lower blood pressure in menopausal women with hypertension.